Electrical and optical properties of semiconducting metal complexes - Yakuphanoğlu, Fahrettin; Dagdelen, F; Aydogdu, Y; Aydogdu, A; Sekerci, M (Elsevier, 2003)
The electrical conductivity, crystal structure, thermoelectric power, thermal conductivity and optical proper-ties of newly synthesized Cu(II), Ni(II) and Co(II) complexes have been investigated. The crystal structure of the complexes was carried out by powder X-ray diffraction (XRD). XRD show that samples are polycrystalline. The conduction mechanism was determined by activation energy process. The electronic parameters of the complexes were calculated, such as, activation energy E for dc conductivity and the density of localized states at the Fermi level N(E-F). The electrical conductivity measurements exhibit three-dimensional variable hopping conduction. The mechanism of the optical absorption follows the rule of direct transition. As a result, it is interpreted that the samples show semiconducting behavior as their conductivity increases with increasing temperature and they have direct optical band gap. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: semiconducting metal complexes; crystal structure; electrical properties; optical properties